2007
DOI: 10.1111/j.1439-0507.2007.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Naildex: pilot evaluation of an onychodystrophy severity instrument

Abstract: SummaryA valid and reliable measure that captures onychodystrophy disease severity is important for both clinical and research applications. Three hundred and twenty-two patients at two Veterans Affairs Medical Centers with clinical evidence of onychodystrophy suggesting onychomycosis (at least 25% in a distal subungual pattern) were examined using Naildex parameters. Naildex scores were calculated by a combination of: per cent of each nail infected, area of each nail and number of infected nails. Patients als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Several studies demonstrate that nail diseases, albeit affecting a rather small portion of the body surface might cause significant impairment of QoL (13,(25)(26)(27)(28)(29). Comparing onychophagia with onychomycosis or nail psoriasis, the impairment in onychophagia patients, based on NailQoL, was smaller than in the 2 latter conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies demonstrate that nail diseases, albeit affecting a rather small portion of the body surface might cause significant impairment of QoL (13,(25)(26)(27)(28)(29). Comparing onychophagia with onychomycosis or nail psoriasis, the impairment in onychophagia patients, based on NailQoL, was smaller than in the 2 latter conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Extent of nail involvement, nail thickening, onycholysis, clinical presentation, proximity to the matrix, presence of dermatophytoma, and factors influencing nail growth, such as the location (fingernail versus toenail) and age of the patient, have been used to design severity index scores. [76][77][78][79] Unfortunately, the severity of the infection at baseline is not always reported in clinical trials, and in cases where it is reported, there is no standardization enabling cross-study comparisons. Indeed, severity was reported as matrix/lunula involvement, mild to severe, percentages of affected nail area, millimeters of healthy nail, and severity index score.…”
Section: Treatment Choice Based On the Severity Of The Infectionmentioning
confidence: 99%
“…Этому может способствовать разочарование наших коллег поисками более точных средств диагностики, особенно неудачами европейских систем ПЦР [41], и последовательным неприз нанием четырех европейских и американских систем клинической оценки онихомикоза [42,43,44].Отсутствие консенсуса зарубежных дер матологов в отношении достоверных клини ческих признаков и предикторов эффективно сти лечения онихомикоза позволяет разным авторам выдвигать собственные критерии оценки. В их число могут входить площадь и глубина поражения, его специфическая локали зация в пределах ногтя, наличие особых редких клинических форм или иные клинико эпидеми ологические факторы, не имеющие непосред ственного отношения к наблюдаемой картине онихомикоза -например, иммунодефицит, са харный диабет, травма и патология стопы [37].…”
Section: как улучшить контроль излеченности?unclassified